Microcredit as a strategy for poverty reduction: a case study of the Sudan - Eissa, Garoot Suleiman (2012)

(untitled)
Sudan is a low income country characterized by high incidence of poverty which currently stands at about 46%. This situation is paradoxical in view of its substantial resource endowments. Sudan government has continued to introduce programmes aimed at alleviation of poverty which were generally characterized by lack of effectiveness. Shortage of investible funds was an important cause of perpetuation of poverty. The traditional approach towards poverty reduction centered on national development programmes designed to enhance economic growth and improve the standards of living. In addition the Islamic institution of Zakat was utilized to assist poor families start income generating projects. However, recently a more ambitious poverty focused microcredit programme has been launched. Thus, billions of dollars were earmarked for microcredit to help the poor obtain investible resources which can be directed towards starting income generating projects or upgrading and modernizing present undertakings. Several institutions were entrusted with implementation with commercial banks as the main lending institutions. This paper argues that today there is no shortage of funds earmarked for microfinance in the Sudan. But the prevailing institutional inadequacies would not allow such substantial outlays to have much impact on poverty reduction. The paper reviews the history of microcredit and microfinance in the country; highlights the role of different institutions in provision of microcredit. Present banking arrangements are deemed unsuitable for microcredit or microfinance. Other public sector institutions lacked capacity to engage in microcredit. Zakat Chambers and NGOs have capacity and experience in dealing with the poor but lack resources. An attempt is made in this paper to figure out the possible policy outputs. Recommendations center on institution building and enhancement of administrative capacity for all institutions so that microcredit programmes can bear fruit to benefit the poor and contribute to the country’s economic growth.